Enhancing MSMEs with Digital Marketing to increase Business Competitiveness and Sustainability - Sutikno Sutikno; Dede Sahrul (Community Service Akseprin Journal, 2025)
Micro, Small, and Medium Enterprises (MSMEs) constitute the foundation of the Indonesian economy. Nonetheless, numerous MSMEs have obstacles in accessing a broader market, particularly in the current digital age. This article examines ideas for empowering MSMEs through online marketing to enhance their competitiveness and sustainability. This project aims to identify barriers, develop effective training models, and assess the effects of online marketing deployment on enhancing revenue and broadening the market reach of MSMEs. The methods used included reviewing existing literature and conducting surveys with MSME participants, followed by both detailed qualitative and quantitative analyses. The study's findings indicate that organised training and mentoring in digital platform utilisation, social media optimisation, and the creation of compelling marketing materials can substantially enhance the competitive capacities of MSMEs in the online marketplace. This article aids in the formulation of policies and initiatives aimed at empowering MSMEs in a more focused and sustainable manner.